Hubungan Sosial Ekonomi Nelayan Lokal dan Nelayan Pendatang di Indonesia Bagian Timur - Lan, Thung Ju (Jurnal Masyarakat dan Budaya, 1998)
The Competition between local fisherman and new comers is mostly assumed to create conflicts. By comparing fisherman of Bebalang & Beo in North Sulawesi with those of Hitu & Sathean in Maluku and those of Tobati & Enggros in Teluk Yotefa, Iran Jaya. We can see that it is not always the case. Homogenety-Heterogenetiy as well as openness-closeness of a fishing community plays an important role in developing competition into (physical) conflicts.